1976
DOI: 10.1063/1.322516
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature polarization in impure SrTiO3 ceramics

Abstract: Properties of stacked SrTiO3/Al2O3 metal-insulator-metal capacitorsMeasurements of the temperature dependence of the dielectric constant and polarization in a constant field have been made on nominally pure SrTi0 3 ceramics and SrTi0 3 ceramics containing vanadium and niobium impurities. The peaks in the dielectric constant and the remanent polarization observed are apparently not due to a ferroelectric or antiferroelectric transition but rather to the presence of a thermoelectret state existing for permanent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

1976
1976
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
1
4
0
1
Order By: Relevance
“…In single crystals of pure SrTiO 3 departures from the simple paraelectric state have been found below 50 K [21,22]. Siegwarth and Morrow [23] suggested that the apparent transitions both in single-crystal and in ceramic SrTiO 3 are due to electret states associated with impurities. Muller and Burkard [24] lowered the temperature of single crystals of SrTiO 3 to 0.035 K without finding evidence of a ferroelectric state.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…In single crystals of pure SrTiO 3 departures from the simple paraelectric state have been found below 50 K [21,22]. Siegwarth and Morrow [23] suggested that the apparent transitions both in single-crystal and in ceramic SrTiO 3 are due to electret states associated with impurities. Muller and Burkard [24] lowered the temperature of single crystals of SrTiO 3 to 0.035 K without finding evidence of a ferroelectric state.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…where P and E are simply the magnitudes of the polarization and electric field vectors. The expression (8) is just that used in the simplest form of the Devonshire theory. Although we need to take account of anisotropy within the ferroelectric region, we shall use the simple isotropic expression within the paraelectric region that is our prime interest.…”
Section: The Isotropic Approximationmentioning
confidence: 99%
“…There are some reported measurements of the properties of mixed strontium-barium titanates in the literature [8][9][10], but these are not extensive enough to allow reliable estimation of the variations of the relevant model parameters with composition. We have therefore carried out a series of measurements on the whole range of compositions of these materials in ceramic form, and the results are reported in a companion paper [11] in which full details are given.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Так, наприклад, у роботi [14] спостерiгали частотну залежнiсть дiелектричної проникностi на керамiчних зразках титанату стронцiю, легованого лантаном. А в роботi [15] виявлено дiелектричну релаксацiю на керамiцi титанату стронцiю, легованого ванадiєм. Оскiльки титанат стронцiю також є вiртуальним сегнетоелектриком i за багатьма властивостями подiбний до танталату калiю, на основi вказаних робiт автори [16] вважають, що у керамiчних зразках танталату калiю теж присутнi домiшки (наприклад, ванадiю), якi спричиняють появу максимуму у залежностi ε(T ) i характернi осо- Якiсне порiвняння спектрiв порошкiв i керамiчного зразка КТаО 3 iз спектрами реактивiв Ta i KNO 3 дозволяє висловити припущення про те, що сигнали у продуктi синтезу складаються з сигналiв вiд центрiв, якi знаходяться у реактивах.…”
Section: результати та їх обговоренняunclassified